The Role of Attitude in Mediating Consumer Knowledge Influence towards the Purchase Intention of Green Product - Wulandari,, A.A Sagung Ayu; Rahyuda, I Ketut; Yasa, Ni Nyoman Kerti (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2015)
Protecting the environment has become a main idea for some modern companies in applying the green marketing strategy. Many consumers perceive that a product with natural raw material can give a better benefit both in terms of health issue and environment. The purpose of this study is to find out the role of attitude in mediating consumer knowledge influence towards the purchase intention of green product Ever-E 250 in Denpasar.The samples were 110 respondents from all over Denpasar taken with the purposive sampling method and path analysis. The result of the study shows that consumer knowledge has significant and positive influence towards the attitude and purchase intention of green product Ever-E 250. The attitude variable has been proven to be able to mediate consumer knowledge influence towards the purchase intention of green product Ever-E 250 in Denpasar significantly, while the mediation happen is partial, so that the attitude variable functions as a mediator of consumer knowledge influence towards the purchase intention of green product.